2003
DOI: 10.1002/bit.10528
|View full text |Cite
|
Sign up to set email alerts
|

Expression and secretion of the heterodimeric protein interleukin‐12 in plant cell suspension culture

Abstract: It has been suggested that plant cell culture is the most suitable system for producing small-to-medium quantities of specialized, expensive, and high-purity proteins. Here, we report that a heterodimeric protein, human interleukin-12 (hIL-12), was expressed and secreted into culture medium in a biologically active form. A transgenic plant expressing hIL-12 was constructed by sexual crossing of plants that expressed each subunit of the protein. From a piece of transgenic plant, callus was induced and cell susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Although secretion of large protein complexes by cultured plant cells depends on a number of factors, and it is not always feasible, several recent studies have indicated feasibility of secretion of large recombinant proteins in plant cell cultures. Notable examples include the secretion of a 155-kDa IgG1 in tobacco cell culture (albeit its modest accumulation in the medium [Sharp and Doran, 2001]) and the secretion of a 75-kDa heterodimeric protein, human interleukin-12 (hIL-12) (Kwon et al, 2003). In the event direct GFP fusion hampers protein secretion, modifications or alternatives to protein fusion may be sought.…”
Section: Discussionmentioning
confidence: 99%
“…Although secretion of large protein complexes by cultured plant cells depends on a number of factors, and it is not always feasible, several recent studies have indicated feasibility of secretion of large recombinant proteins in plant cell cultures. Notable examples include the secretion of a 155-kDa IgG1 in tobacco cell culture (albeit its modest accumulation in the medium [Sharp and Doran, 2001]) and the secretion of a 75-kDa heterodimeric protein, human interleukin-12 (hIL-12) (Kwon et al, 2003). In the event direct GFP fusion hampers protein secretion, modifications or alternatives to protein fusion may be sought.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports of bioproduction of mammalian IL-12 in plants ( GutierrezOrtega et al, 2004GutierrezOrtega et al, , 2005Kwon et al, 2003) yielded IL-12 at very low levels and demonstrated only partial IL-12 activity. In contrast, the Cramer/Dolan laboratory has developed tobacco lines that yielded high levels of murine that show equivalent bioactivity to animal cell-derived mIL-12 in both in vitro assays and in mouse vaccination studies (Liu, 2006;Liu et al, 2008).…”
mentioning
confidence: 92%
“…More than 80% of hIL-12 was secreted into the medium with less than 20% remaining in the cells (Kwon et al 2003). Although the cells continued vigorous growth, the concentration of total and secreted concentration of IL-12 dropped precipitously to about 10 mg g À1 FW, while the intracellular levels increased to about 55 mg g À1 FW at day 11, well into stationary phase.…”
mentioning
confidence: 96%
See 2 more Smart Citations